Model Pariwisata Digital dalam Transformasi Tata Kelola Objek Wisata Berbasis Masyarakat Lokal di Kabupaten Enrekang - Muhammad Hidayat Djabbari; Dewi Sulfa Saguni; Fetni; Widyawati (Halu Oleo University, 2025)
This study aims to analyse the digital tourism model in the transformation of local community-based tourism management in Enrekang Regency, using the AIDDA model approach (Attention, Interest, Desire, Decision, and Action) and technological transformation related to digital technology usage. The research employs qualitative methods with a descriptive approach. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis utilised interactive model analysis to gather insights from key informants involved in the tourism industry. The findings show that the AIDDA model approach at each stage is interconnected in attracting visitors to tourist sites. Promotion through social media, supported by positive testimonials and easy accessibility, can influence tourists' interest and decision to visit. In terms of technological transformation in Enrekang Regency, tourism apps and digital payments have supported tourism management, although challenges such as limited human resources and infrastructure continue to hinder the development of digital tourism in Enrekang. Additionally, empowering local communities through digital training has helped in the transformation of digital tourism management.